Розробка експериментального зразка пульсаційного гомогенізатора молока - Кюрчев, Сергій Володимирович; Самойчук, Кирило Олегович; Ялпачик, Володимир Федорович; Kiurchev, Serhii; Samoichuk, Kyryl; Yalpachyk, Volodymyr (Запоріжжя : 2023, 2023)
UA: Однією з актуальних задач харчової промисловості є розробка високоефективних гомогенізаторів-диспергаторів рідких емульсій зі зниженими енерговитратами. Одним з перспективних напрямів вирішення цієї задачі є дослідження, розробка та впровадження пульсаційного гомогенізатора. Принцип дії такої машини – диспергування жирової фази при інтенсивному коливальному русі поршня за рахунок створення високих прискорень емульсії, які виникають в отворах поршня. Важливим етапом цього завдання є розробка експериментального зразка дослідного гомогенізатора. Тому мета даної статті – створення експериментального зразка пульсаційного гомогенізатора, придатного для проведення експериментальних досліджень процесу пульсаційної гомогенізації молока. В статті наведені вимоги до розробленої установки, характеристики, необхідні розрахунки основних вузлів машини (технологічні, конструктивні та гідравлічні). Наведено фото розробленої установки та описаний принцип її дії. Розроблений експериментальний зразок необхідний дослідникам процесів гомогенізації та диспергування емульсій в харчовій, переробній, хімічній галузях промисловості а також сільському господарстві при проектуванні та будівництві машин відповідних галузей. EN: One of the urgent tasks of the food industry is the development of highly efficient homogenizers-dispersers of liquid emulsions with reduced energy consumption. One of the promising directions for solving this problem is the research, development and implementation of a pulsating homogenizer. The principle of operation of such a machine is the dispersion of the fat phase during intensive oscillatory movement of the piston due to the creation of high emulsion accelerations that occur in the piston holes. An important stage of this task is the development of an experimental sample of the experimental homogenizer. Therefore, the purpose of this article is to create an experimental sample of a pulsating homogenizer suitable for conducting experimental studies of the pulsating homogenization process of milk. Experimental studies are the most responsible stage, capable of predicting the prospects and expediency of introducing a pulsating homogenizer instead of existing valve homogenizers with a specific energy consumption of 7 kWh/t of finished product. The article provides the requirements for the developed installation, characteristics, necessary calculations of the main components of the machine (technological, structural and hydraulic). A photo of the developed installation and the principle of its operation are described. The main calculations of the experimental sample of the pulsating homogenizer are presented. For an installation with a productivity of 500 kg/h. according to the calculation, the USHM WD2400-150 unit with a nominal power of 2.4 kW and a rotation frequency of 11,000 rpm was chosen as the drive. The total maximum power consumption of the experimental sample of the pulsating homogenizer is 2900 W. The developed experimental sample is necessary for researchers of the processes of homogenization and dispersion of emulsions in the food, processing, and chemical industries, as well as in agriculture during the design and construction of machines in the relevant industries.
Development of the experimental sample of the pulsation milk homogenizer
Keywords: гомогенізація; диспергування молока; емульсія; дисперсність; експериментальний зразок; пульсаційний гомогенізатор; homogenization; dispersion of milk; emulsion; dispersion; experimental sample; pulsating homogenizer